PENGEMBANGAN SSP TEMATIK INTEGRATIF BERBASIS LVEP UNTUK PENGUATAN KARAKTER NASIONALISME PESERTA DIDIK SD - Indah Perdana Sari dan An-Nisa Apriani (Universitas PGRI Yogyakarta, 2020)
AbstractThis study aims to (1) produce an Integrative Thematic SSP based on the Living Values Education Program (LVEP) for Strengthening the Nationalism Character of Elementary Students and (2) determine the effectiveness of the LVEP-based Thematic Integrative SSP to improve understanding of the nationalism character of elementary school students. This type of research is Research & Development (R&D) with a development model from Borg & Gall. This model consists of 10 stages. Data collection techniques used are guidelines for product assessment, observation, questionnaires, and interviews. Data collection instruments used were product assessment guidelines, observation guidelines, questionnaires, and interview guidelines. The results showed the Integrative Thematic SSP based on the Living Values Education Program (LVEP) for the Strengthening of Nationalism Characteristics of Elementary School Students at the initial coaba test stage was known to P 0,000 <0.05 meaning there was a difference between the average observations of the nationalism character values before and after the study, in the test try the field known P 0,000 <0.05 means that there is a difference between the average results of observations of the value of nationalism character before and after research, and in the field test it is known that P 0,000 <0.05 means there is a difference between the average results of observing the value of nationalism characters before and after research. Furthermore, the student assessment sheet on the practicality of the SSP that was developed was categorized as